Ultra-processed foods and cancer risk - Kliemann, Nathalie (2022)
Funding Information: This work was supported by Cancer Research UK [Ref: C33493/A29678] and World Cancer Research Fund International [Ref: IIG_FULL_2020_033]. Publisher Copyright: © 2022, The Author(s), under exclusive licence to Springer Nature Limited.